2016
DOI: 10.1007/s10439-016-1639-x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Astrocytic Thrombospondin-4 Induced by Excitatory Neuronal Signaling Mediates Pain After Facet Capsule Injury

Abstract: Thrombospondin-4 (TSP4) is a synaptogenic molecule that is upregulated in the spinal cord after painful facet joint injury and may contribute to spinal hyperexcitability. However, the mechanisms leading to increased spinal TSP4 are unclear. Because primary afferent activity is critical in the development of spinal hyperexcitability after facet joint injury, this study evaluated the role of afferent firing in the increase of spinal TSP4 and excitatory synapses. Intra-articular bupivacaine was administered immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The effect of TSP-4 was due to decreasing high-voltage-activated calcium current and increasing low-voltage-activated calcium current in dorsal root ganglia (DRG) (53) by activating its receptor α2δ-1 calcium channel subunit (54). Further investigation of this new function of TSP-4 in various models (51, 122, 123) suggested that TSP-4 could become a potential target for development of antagonists with therapeutic potential for target-specific neuropathic pain management.…”
Section: Role Of Tsp-4 In the Nervous Systemmentioning
confidence: 99%
“…The effect of TSP-4 was due to decreasing high-voltage-activated calcium current and increasing low-voltage-activated calcium current in dorsal root ganglia (DRG) (53) by activating its receptor α2δ-1 calcium channel subunit (54). Further investigation of this new function of TSP-4 in various models (51, 122, 123) suggested that TSP-4 could become a potential target for development of antagonists with therapeutic potential for target-specific neuropathic pain management.…”
Section: Role Of Tsp-4 In the Nervous Systemmentioning
confidence: 99%
“…THBS4 plays a role in tendon repair [Subramanian et al, 2014] and regulates stem cell fate and differentiation potential [Islam et al, 2016]. This protein is also involved in local signaling of the nervous system [Crosby et al, 2016]. In the present study, both cell types originated from adipose tissue.…”
Section: Discussionmentioning
confidence: 83%
“…These results indicated that TSP2 may be secreted by macroglia cells and participate presynaptic proteins changes induced by EHP. Except for TSP2 secreted by reactive macroglia cells, recent studies demonstrated that TSP4 may also generated by reactive astrocytes and contribute to synaptogenesis after injury[ 47 , 48 ]. Therefore, clearly further studies are needed to explore the synaptogenic roles of different increased TSPs after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to expect that strategies targeting the macroglia-TSP2-α2δ-1 pathway to regulate presynaptic changes of retinal neurons after EHP may contribute to the recovery of visual function. Also, we suspect that another way to protect the visual pathway is to stimulate postsynaptic changes, such as those induced by glypicans, which can arouse the response of the postsynaptic components in response to the presynaptic synaptogenesis events[ 48 , 49 ]. Besides the presynaptic mechanism of TSP2/α2δ-1 pathway, we speculate macroglia might play a key role in a complementary mechanism of postsynaptic changes of retinal neurons after EHP, which requires further experimental exploration.…”
Section: Discussionmentioning
confidence: 99%